Profit : Plan for It, Get It-The Entrepreneurs Handbook. - Hutter, H. R. (Entrepreneurship and small business management collection., 2018)
This book is designed to help an entrepreneur increase his profit by introducing how he can use a simplified profit-and-loss statement of four to ten items as a tool to analyze his business from a financial perspective. He will be shown how he can use these items in a formula to help him plan and make decisions for future growth and profit. We will discuss skills and practices that have been used to improve sales, management, leadership, and planning skills. Hopefully, this book will help you improve your profitability.